Qualidade ambiental das nascentes do Córrego Grande na Bacia do Ribeirão Ponte de Pedra (Rondonópolis, Mato Grosso) - Ereio, Patrícia Karina Barbosa (2017)
The springs are part of the river systems being important for the maintenance of the hydrological and biological balance. This research aimed to analyze the relationship between land use and the environmental quality of the Córrego Grande springs belonging to the Ponte de Pedra river basin in the municipality of Rondonópolis, Mato Grosso. The springs analyzed are located in the area of the Carimã settlement, where there are diversified uses of land, and whose environment is formed by conservation units and rural properties where intensive farming is practiced. A survey of the history of land use in this settlement was conducted through an interview using the method of communicative investigation (Brazil Platform No. 2,034,719). The drainage network and the location of the springs were initially delimited from the processing of the Digital Elevation Model (DEM) and processed in the environment (SIG). Said DEM was produced from the SRTM / TOPOTADA image scene. The extraction of the basins and drainage network was based on TerraHidro version 4.2.2. It was evaluated and mapped the land uses in the Córrego Grande basin and Ponte de Pedra stream, and calculated the Vegetation Cover Index (ICV) in the surroundings of the sources through the GIS using orbital images / TM Landsat-8 with spatial resolution of 15 meters . The ICV subsidized the evaluation of the degree of preservation of the Permanent Preservation Areas (APP) and the macroscopic analysis of the environmental quality of the sources. In the field, the data generated by orbital images were evaluated, and the macroscopic evaluation was performed to obtain the Nascent Environmental Quality Index (IQAn). The IQAn factors evaluated were the transparency and odor of water, presence of litter in the surroundings, oiliness in the water, presence of erosion near the springs, silting of the source or at the beginning of the watercourse, impoundment, vegetation cover in the APP area , presence of cattle, anthropic uses (pipes, water wheels, containment boxes), protection in the spring environment, proximity to residences (septic tanks), type of occupation in the surroundings (pasture, agriculture, fish farming and others). The map of the Inland Influence Vulnerability Index (IVIAP) of the Córrego Grande basin was generated through the GIS, with hydrological, geomorphological and plant density data through a medium-high resolution CBER-4 image with a resolution of 5 meters. Each spring received a classification of ICV, IQAn and IVIAP. Throughout the history of the Settlement the change in the profile of uses of the land happened through the exploration of the familiar agriculture, the cattle raising and the tourist exploration. The ICV in the surroundings of the 35 springs analyzed in the Córrego Grande basin showed that 23 can be classified as excellent, 3 very good, 3 good, 3 reasonable, 1 bad, and 2 bad ones. IQAn ranked seven springs as good, eight good, eight reasonable, ten bad and two bad. The main degradation factors identified were cattle presence, erosion processes and absence of protection. The springs classified by IQAn as excellent, good and reasonable presented the highest IVIAP, being more susceptible to water contamination by agrochemical uses, a fact that has been occurring for more than 20 years in the Córrego Grande basin. In view of the results it is possible to affirm that maintaining the APPs in the surroundings of the springs is fundamental to guarantee the good environmental quality, but also it is necessary to increase the care with the land uses in the areas of recharge. It is a region where the agricultural production method is separated from a management plan, which has contributed to the reduction of the exfiltration of the waters and, therefore, there have been damages to the quality of the springs of the Great Stream. This environmental quality is the result of the interaction of various physical, chemical, biological and social processes, over time, where all are co-responsible for the current quality.